2019
DOI: 10.3389/fmars.2019.00275
|View full text |Cite
|
Sign up to set email alerts
|

Primary Productivity Dynamics in the Summer Arctic Ocean Confirms Broad Regulation of the Electron Requirement for Carbon Fixation by Light-Phytoplankton Community Interaction

Abstract: Zhu et al. Phytoplankton Photophysiology in Arctic Ocean community structure integrates past and immediate environmental histories and hence may be a better broad-scale predictor of K C than specific environmental factors such as temperature and nutrients. We provide a novel algorithm that may enable broad-scale retrieval of CO 2 uptake from FRRf with knowledge of light and phytoplankton community size information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 99 publications
(190 reference statements)
2
16
0
Order By: Relevance
“…Moreover, compared with the theoretical maximum value (0.65) determined by Kolber and Falkowski (1993), approximately 40% of the PSII reaction centers appear to have been inactive. Zhu et al (2019) also reported that the F v / F m in the Chukchi Borderland was approximately 24% lower than in the CS waters, which was similar to the results of this study. Meanwhile, the F v / F m observed off the coast of the Arctic Ocean is known to remain high (≥0.50) throughout the year, except immediately after the spring bloom (Aardema et al, 2019; Kulk et al, 2018; McMinn & Hegseth, 2004; Mills et al, 2018; Mosharov et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, compared with the theoretical maximum value (0.65) determined by Kolber and Falkowski (1993), approximately 40% of the PSII reaction centers appear to have been inactive. Zhu et al (2019) also reported that the F v / F m in the Chukchi Borderland was approximately 24% lower than in the CS waters, which was similar to the results of this study. Meanwhile, the F v / F m observed off the coast of the Arctic Ocean is known to remain high (≥0.50) throughout the year, except immediately after the spring bloom (Aardema et al, 2019; Kulk et al, 2018; McMinn & Hegseth, 2004; Mills et al, 2018; Mosharov et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, nutrient uptake rates and carbon‐specific photosynthesis vary with changes in the phytoplankton community structure (Cermeño et al, 2005; Hein et al, 1995; Uitz et al, 2008). Recently, the physiological status of phytoplankton in the Arctic Ocean was also known to be affected by light availability and phytoplankton community structure under nitrogen limitation (Kulk et al, 2018; Mills et al, 2018; Mosharov et al, 2019; Zhu et al, 2019). However, these studies were result of a year limited to coastal and shelf regions of the Arctic Ocean, and lacked experimental information on the extent to which physiological conditions were reduced by nitrogen limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, variability in irradiance level was another primary driver of variability in F v /F m , F q /F m , and F q /F v in the WPO (p < 0.05; Figure 7). The depth-specific fitting values of these light absorption characteristics we observed were higher at the subsurface (Figure 4), and one important explanation for this is that the interactive effects of light and nutrient levels lead to an increase in these light absorption parameters (Moore et al, 2006;Suggett et al, 2009;Zhu et al, 2019). In contrast, the strong effects of excess irradiance pressure and limitation by nutrients in the surface inhibited the F v /F m , F q /F m , and F q /F v (Figure 4; Schuback et al, 2017;Wei et al, 2019b).…”
Section: Physiological and Ecological Responses Of Photosynthetic Promentioning
confidence: 75%
“…While our dataset is too small to draw general conclusions, our experimental results allow us to gain some physiological and ecological insights into how the dominant environmental constraints and algal species regulate the light absorption characteristics and electron transport and what is the key in driving the dynamics of WPO primary productivity. Light absorption parameters F v /F m and F q /F m showed positive correlations with size-fractionated Chl a (p < 0.01; Figure 7), suggesting that the light absorption characteristics in photosynthetic process are potentially controlled by the variability in phytoplankton communities (Suggett et al, 2009;Schuback et al, 2017;Zhu et al, 2019;Wei et al, 2019b). Certainly, this result appears to be exemplified to differing degrees by the significant relationships between F v /F m and large diatoms (cells > 2 µm), picosized Pro and PEuks (see Figure 8A below).…”
Section: Physiological and Ecological Responses Of Photosynthetic Promentioning
confidence: 99%
See 1 more Smart Citation